Direct Numerical Simulation of conjugated heat transfer between a spherical particle rolling over a planar surface. (5th July 2018) - Brösigke, Georg; Herter, Alexander; Rädle, Matthias; Repke, Jens-Uwe
Highlights: Influence of turbulence on heat transfer by 3D Direct Numerical Simulation. Direct calculation of heat transfer by boundary conditions without correlations. Resolution of all involved phases. Calculation of local heat transfer coefficients. Abstract: The heat transfer between particles and walls occurs in several industrial processes. Simplified models are applicable within their range of validity and give satisfactory results for known systems. On the other hand, for developing innovative apparatus with Process Intensification and energy efficiency in mind, e.g. a heat recovery system for biogas plants, it is crucial to understand the basic mechanisms. This work aims at reaching a fundamental understanding of the occurring transport phenomena both qualitatively and quantitatively under the presence of turbulence, since turbulence is known for enhancing transport phenomena. A highly resolved finite volume method is applied carrying out Direct Numerical Simulation (DNS) of fluid dynamics and heat transfer simultaneously. The performed simulations, for the first time, describe all involved physical phenomena of a solid particle moving within a fluid phase across a fixed solid phase on continuum level, where all involved phases (particle, gas phase and plate) are resolved with finite volumes. Global and local heat transfer coefficients are presented for spherical particles in a diameter range of 1–2 mm. Global heat transfer coefficients between sphere and plate lie in a range between 531 and 807 W/m 2 K, whereas local values of up to 40, 000 W/m 2 K are observed. The particle Reynolds Number is varied in a range from 3 to 500 and covers flow regimes from laminar state up to transition to turbulent flow. Influence of turbulence on heat transfer mechanisms is discussed in this paper and it is demonstrated that the conductive mechanism is mainly responsible for heat transfer between sphere and plate, whereas the conductive mechanism dominates transport between sphere and gas phase.